2012
DOI: 10.1074/jbc.m111.319145
|View full text |Cite|
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor β/δ Induces Myogenesis by Modulating Myostatin Activity

Abstract: Background: PPAR␤/␦ has been implicated in muscle regeneration; however the signaling mechanism(s) is unclear. Results: Activation of PPAR␤/␦-promoted Gasp-1 expression blocked myostatin activity and enhanced myogenesis. Conclusion: Activation of PPAR␤/␦ led to inhibition of myostatin activity and thus increased myogenesis. Significance: PPAR␤/␦ agonists are novel myostatin antagonists that have potential benefits toward improving postnatal muscle growth and repair.Classically, peroxisome proliferator-activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…Interestingly, the promoter of myostatin-2a does not appear to contain any PPARREs, and experimental data failed to reveal any changes in the transcription of this paralog. At the protein level, PPARβδ has been shown to upregulate Gasp-1 expression, a protein that attenuates the actions of myostatin (Bonala et al 2012). Further, crosstalk between PPARγ and myostatin signaling has been demonstrated in human mesenchymal stem cells (hMSCs) (Guo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the promoter of myostatin-2a does not appear to contain any PPARREs, and experimental data failed to reveal any changes in the transcription of this paralog. At the protein level, PPARβδ has been shown to upregulate Gasp-1 expression, a protein that attenuates the actions of myostatin (Bonala et al 2012). Further, crosstalk between PPARγ and myostatin signaling has been demonstrated in human mesenchymal stem cells (hMSCs) (Guo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we investigated the cellular and molecular mechanisms deregulated by Gasp-1 overexpression to provide a detailed muscle phenotype characterization. Previous studies have shown that GASP-1 is capable of binding both myostatin and GDF-11 to inhibit their canonical pathway in vitro [29,38]. Mice lacking Gasp-1 exhibit only a slight muscle atrophy without an axial skeletal phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Further, inhibition of the canonical MSTN-Smad pathway by WFIKKN2 was demonstrated in an in vitro myoblast cell line and led to an increase in myoblast differentiation and proliferation [8,37]. The WFIKKN function in muscle is also consistent with ovine polymorphisms present in intron 1 and 3 0 UTR region of the WFIKKN2 gene in 8 sheep breeds.…”
Section: Role Of Wfikkn In Mstn and Gdf11 Inhibitionmentioning
confidence: 71%
“…Regarding the regulation of the expression of the WFIKKN genes, a functional PPARB/G (peroxisome proliferator-activated receptor beta/gamma) site in the promoter of murine Wfikkn2 was found to be involved in the regulation of Wfikkn2 expression [8]. Further, increased expression of Pparg in mice overexpressing Wfikkn2 [7] provided some evidence of auto-regulation of Wfikkn2 gene expression by PPARB/G.…”
Section: Expression Pattern and Regulation Of Wfikkn1 And Wfikkn2mentioning
confidence: 96%
See 1 more Smart Citation